Impact of Environmental Regulations on the manufacturing Sector of India - Nayak, Ajit (2008)
The growing concerns over the depleting environment and the growing pollution levels have raised concerns over the preservation of the environment. Industrialization and the growth of the manufacturing sector have had an impact on the environment. The utilization of natural resources has grown over the years, and most of the industrial developments in the past few year have been due to unplanned urbanization in India. The environment is a major concern globally and the pressure is on the manufacturing sector to reduce wastage and increase utilization to reduce its effect on the environment. The technological changes have bought about major reformations in the manufacturing sector and companies globally are developing new and innovative processes and techniques to comply with the regulations. Over the past few years the environmental regulations globally have got stricter and hence companies now have no choice by comply by the regulations. However there are a lot of uncertainties that can effect a firms decision to comply with the regulations. International competition has also has forced companies to comply with the regulations as it helps create a green image. In this study I have tried to analyze the impact environmental regulations can have on a firm's performance. The importance of compliance to the regulations is growing, and the companies seem to understand the importance of environmentally sustainable practices to comply with the regulations. None the less very few companies have efficient environmental management practices in place. The growing need and importance of complying with the environmental regulations could influence many more firms in India to comply with the regulations.